2012
DOI: 10.1016/j.ajic.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

How the H1N1 influenza epidemic spread among university students in Japan: Experience from Shinshu University

Abstract: Background: A worldwide outbreak of influenza A/H1N1 occurred in 2009. Little information is available regarding how the epidemic spread among young people, who comprised the majority of individuals infected with this virus. We therefore assessed the route of transmission of H1N1 among university students at Shinshu University, Japan. Methods: A total of 11,424 students were monitored from August 2009 to March 2010, and those who were diagnosed with confirmed, probable or suspected H1N1 at a hospital or clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…At the end of the pandemic, it became clear that H1N1 had spread more among younger people than older people [3][4][5][6][7][8], and there were many infections among schoolchildren [9][10][11]. Measures instituted to prevent the transmission of H1N1 included school closures [12][13][14][15].…”
mentioning
confidence: 99%
“…At the end of the pandemic, it became clear that H1N1 had spread more among younger people than older people [3][4][5][6][7][8], and there were many infections among schoolchildren [9][10][11]. Measures instituted to prevent the transmission of H1N1 included school closures [12][13][14][15].…”
mentioning
confidence: 99%
“…This information was thought to be useful for rapid implementation of adequate infection control measures at university organizations [12]. We also reported epidemiological studies among university organizations in Japan [13][14][15][16] and the results indicated that many students were infected with H1N1 and the specific transmission route was identified among university students in Japan. However, in Japan, although the information of H1N1 at educational organizations was distributed broadly it was not featured at universities or colleges in great detail.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, the proportion of H1N1 influenza patients among university students is probably robust regardless of country. The authors reported that H1N1 was spread through clubs, close friends, apartments, or classrooms during the epidemic period [14]. The transmission routes were investigated by interviews.…”
Section: Descriptive Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The designated person at the university interviewed and recorded the characteristics of each student, including name, gender, age, grade and faculty, as well as information on H1N1 infection, including the dates of fever onset and hospital visit, symptoms, the date and route of infection and body temperature. While club activity at the university was suspended several times [18], the school was not closed to university students during this period.…”
Section: Circumstance Of H1n1 Infection and Precaution Measure Takenmentioning
confidence: 99%